Is There a One-Size-Fits-All Approach to Inclusive Growth? : A Case Study Analysis - Balasubramanian, Sriram (IMF Working Papers; Working Paper, 2021)
Is there a one-size-fits-all approach to inclusive growth? We look at four key case studies across advanced and emerging markets-the Nordics, India, Brazil, and Egypt-to try to answer this question. We highlight qualitatively in these countries the key components of inclusive growth models, outcomes from these models, and the road ahead in the respective countries. Some of the analysis focuses on co-operative labor markets in the Nordics, direct benefit transfers in India, the role of social assistance and commodity boom in Brazil, and the inequality puzzle in Egypt. The paper finds that there is a lack of homogeneity among the approaches by these countries and identifies the need for customized solutions to inclusive growth. A one-size-fits-all approach doesn't seem to work. The more customized the inclusive growth model, the better the overall outcome.